Psychological Intervention and Treatment for Posttraumatic Stress Disorder During Pregnancy: A Systematic Review and Call to Action. Issue 3 (19th December 2020) - Stevens, Natalie R.; Miller, Michelle L.; Puetz, Ann‐Kathrin; Padin, Avelina C.; Adams, Natasia; Meyer, Danie J.
Abstract: Posttraumatic stress disorder (PTSD) during pregnancy is a significant global mental health concern that affects up to 1 in 5 trauma‐exposed pregnant women and is associated with an increased risk of adverse maternal and infant complications and health outcomes. This systematic literature review, conducted in accordance with PRISMA guidelines, examined findings from studies of psychological interventions and treatments for prenatal PTSD to inform recommendations for future research. Relevant evidence was identified from reference reviews and electronic databases (i.e., PubMed, Google Scholar, PsychInfo, and Scopus). Included studies reported on the effect of nonpharmacological intervention or treatment of PTSD symptomatology delivered during pregnancy, with at least one postintervention follow‐up collected during pregnancy to assess prenatal treatment outcomes. The systematic review was augmented with a discussion of lower‐level evidence. Of the 954 articles screened, six peer‐reviewed, quantitative reports met the inclusion criteria and featured three empirically based interventions, including two randomized controlled trials: Two psychoeducation interventions for PTSD and one treatment study of interpersonal psychotherapy in trauma‐exposed pregnant women. Effect sizes for PTSD symptom change ranged from small to large, Cohen's d/ ηp 2 = 0.16–0.78. No studies examined evidence‐based PTSD treatments (e.g., exposure therapy, cognitive processing therapy). A risk of bias assessment indicated variability in study quality. This review demonstrates that research on prenatal PTSD symptoms, diagnosis, and treatment is extremely limited despite a clear link between prenatal PTSD and perinatal complications. Early evidence supports further scientific inquiry into psychoeducation, psychotherapy treatments (e.g., exposure therapy), integrated prenatal care approaches, and community‐based approaches. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0211.R1_Stevens_Cantonese Traditional Chinese 妊娠期創傷後壓力症的心理干預和治療:系統綜述和行動呼籲 摘要: 妊娠期間的創傷後壓力症(PTSD)是一個重要的全球心理健康問題, 這影響到五分之一的受創傷影響的孕婦, 並與不良母嬰併發症和健康結果的風險增加有關。這篇系統的文獻綜述, 按照PRISMA指南進行, 研究了產前創傷後壓力症的心理干預和治療的研究結果, 為今後的研究提供建議。從文獻綜述和電子數據庫(PubMed, 谷歌Scholar, PsychInfo, Scopus)中找到相關證據。納入的研究報告了在懷孕期間對創傷後壓力症症狀進行非藥物干預或治療的效果, 在懷孕期間至少收集一次干預後隨訪, 以評估產前治療結果。系統綜述中增加了對低級別證據的討論。在篩選出的954篇文章中, 有6篇經同行評議的定量報告符合納入標準, 其中有3項基於經驗的干預措施, 包括兩項隨機對照試驗。兩項針對創傷後壓力症的心理教育干預, 一項針對暴露於創傷的孕婦的人際心理療法的治療研究。 創傷後壓力症症狀變化的效應大小從小到大不等, Cohen's d/ηp2 = 0.16‐0.78。無研究對基於證據的創傷後壓力症治療(如長期暴露療法、認知加工療法)進行研究。偏倚風險評估表明研究質量存在差異。本綜述表明, 儘管產前創傷後壓力症和圍產期併發症之間存在明確的聯繫, 但對產前創傷後壓力症症狀、診斷和治療的研究卻極為有限。早期的證據支持對心理教育、心理治療方法(如長期暴露療法)、綜合產前護理方法和基於社區的方法進行進一步的科學研究。 Simplified Chinese 妊娠期创伤后压力症的心理干预和治疗:系统综述和行动呼吁 摘要: 妊娠期间的创伤后压力症(PTSD)是一个重要的全球心理健康问题, 这影响到五分之一的受创伤影响的孕妇, 并与不良母婴并发症和健康结果的风险增加有关。这篇系统的文献综述, 按照PRISMA指南进行, 研究了产前创伤后压力症的心理干预和治疗的研究结果, 为今后的研究提供建议。从文献综述和电子数据库(PubMed, 谷歌Scholar, PsychInfo, Scopus)中找到相关证据。纳入的研究报告了在怀孕期间对创伤后压力症症状进行非药物干预或治疗的效果, 在怀孕期间至少收集一次干预后随访, 以评估产前治疗结果。系统综述中增加了对低级别证据的讨论。在筛选出的954篇文章中, 有6篇经同行评议的定量报告符合纳入标准, 其中有3项基于经验的干预措施, 包括两项随机对照试验。两项针对创伤后压力症的心理教育干预, 一项针对暴露于创伤的孕妇的人际心理疗法的治疗研究。 创伤后压力症症状变化的效应大小从小到大不等, Cohen's d/ηp2 = 0.16‐0.78。无研究对基于证据的创伤后压力症治疗(如长期暴露疗法、认知加工疗法)进行研究。偏倚风险评估表明研究质量存在差异。本综述表明, 尽管产前创伤后压力症和围产期并发症之间存在明确的联系, 但对产前创伤后压力症症状、诊断和治疗的研究却极为有限。早期的证据支持对心理教育、心理治疗方法(如长期暴露疗法)、综合产前护理方法和基于小区的方法进行进一步的科学研究。